DEVELOPMENT FOUR-TIER DIAGNOSTIC TEST INSTRUMENTS ON NEWTON’S LAW OF GRAVITATION CONCEPT - IZZAH, NURUL, MADLAZIM (Inovasi Pendidikan Fisika, 2019)
Misconception is knowledge or idea that not in accordance with the scientific knowledge or not agreed upon by scientists. Misconceptions can be found on the concepts of physics, including Newtons Law of Gravitation concept. This paper aim is to develop a four-tier diagnostic test instrument for Newtons Law of Gravitation concept. This developed instrument is amount to 18 questions which contained concept, Including sub material Mass and Weight, Gravitational Field, etc. The type of this research is development research using the ADDIE model. The result of the calculation shows that the developed instrument was declared valid by two validator lecturers with a validity level between (83?95) %. The result of the instrument?s external validity which was tested on 20 students was obtained 15 questions valid and reliable.Keywords: four-tier diagnostic test, misconceptions, Newtons Law of Gravitation